PENGETAHUAN E-WASTE YANG DIPENGARUHI OLEH MEDIA, WORD-OF-MOUTH, PENGGUNAAN MEDIA SOSIAL - Muhammad Fadhlullah; Yanuar Luqman (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2023)
The e-waste issue is an important issue that must be discussed in communication science studies. Environmental communication related to e-waste issues has not received attention and needs to be discussed in more detail. Transmission of communication through media channels is related to influencing public knowledge regarding e-waste issues and its management practices. Efforts to be exposed to news, word-of-mouth communication, and social media usage are expected to influence public knowledge regarding this environmental issue. This research aims to determine and explain the influence of news exposure, word-of-mouth communication, and social media usage on increasing e-waste knowledge among students in Semarang City. The research was conducted using a survey method with an explanatory quantitative approach on a sample of 100 respondents with data analysis using multiple linear regression analysis. The partial research results show that news exposure has a positive influence on increasing e-waste knowledge, word-of-mouth communication does not have a positive impact on improving e-waste knowledge, and social media usage has a positive influence on increasing e-waste knowledge. News exposure, word-of-mouth communication, and social media usage simultaneously have a positive impact on improving e-waste knowledge. Intelligence programs and community empowerment efforts are needed so that the public can participate in e-waste management.